Direct observation of imploded core heating via fast electrons with super-penetration scheme - Gong, T. (Nat Commun, 2019)
Fast ignition (FI) is a promising approach for high-energy-gain inertial confinement fusion in the laboratory. To achieve ignition, the energy of a short-pulse laser is required to be delivered efficiently to the pre-compressed fuel core via a high-energy electron beam. Therefore, understanding the transport and energy deposition of this electron beam inside the pre-compressed core is the key for FI. Here we report on the direct observation of the electron beam transport and deposition in a compressed core through the stimulated Cu Kα emission in the super-penetration scheme. Simulations reproducing the experimental measurements indicate that, at the time of peak compression, about 1% of the short-pulse energy is coupled to a relatively low-density core with a radius of 70 μm. Analysis with the support of 2D particle-in-cell simulations uncovers the key factors improving this coupling efficiency. Our findings are of critical importance for optimizing FI experiments in a super-penetration scheme.